Towards an Enabling Legal and Regulatory Framework for International Franchising Business in Nigeria - Bello, Fatima (ABUAD Law Journal, 2021)
UNCTAD has estimated that around 18 – 21 million people are employed under Non – Equity Modes (NEMs) of production, with the bulk of them being in contract manufacturing, outsourcing, and franchising. 80% of these employments are mostly in developing countries. If well-strategised, NEMs can present massive potential for developing countries such as Nigeria to increase their share of value addition, build productive capacity, integrate the country into the Global Value Chain (GVC), and increase its participation in international trade. Nigeria has signed and ratified the African Continental Free Trade Area (AfCFTA) Agreement, is a member of the WTO, and has integrated Sustainable Development Goals (SDGs) into its development strategy. It seeks to develop its productive capacity through industrialisation, pursue export-led growth through trade under the AfCFTA and increase participation in the GVC. Franchising as a business model is used to mitigate against certain risks, create jobs, and is used as a tool to gain entry into a new and/ or uncertain business environment making it worth exploring to improve international franchising in Nigeria. The research observed that although attempts have been made to woe international franchisors by Nigeria, the sector performed below expectation. The paper finds that the legal and regulatory environment does not create an enabling environment for franchises to thrive, This makes the business environment unattractive for international franchising. Hence, using the doctrinal approach, this paper seeks to analyse the legal and regulatory framework for franchising business in Nigeria to determine how prepared it is to regulate franchising business in Nigeria to assess its capability to support Nigeria, and proffering suggestions on how to improve it to enable Nigeria leverage on it to undergird its industrialisation and export market development.